2011
DOI: 10.3389/fendo.2011.00075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Endocrinology of Aging and Longevity Regulation

Abstract: Hormones regulate growth, development, metabolism, and other complex processes in multicellular animals. For many years it has been suggested that hormones may also influence the rate of the aging process. Aging is a multifactorial process that causes biological systems to break down and cease to function in adult organisms as time passes, eventually leading to death. The exact underlying causes of the aging process remain a topic for debate, and clues that may shed light on these causes are eagerly sought aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 462 publications
(514 reference statements)
0
16
0
1
Order By: Relevance
“…IGFBP-5 may play a role in the pathogenesis of atherosclerosis, which is a process of inflammatory tissue remodeling within the matrix of the arterial wall that is the top cause of cardiovascular disease and aging-related mortality in humans (136). A cross-sectional case-control study found a positive association between circulating IGFBP-5 levels and coronary heart disease (137).…”
Section: Igfbp-5 In Pathology and Disease Statesmentioning
confidence: 99%
See 2 more Smart Citations
“…IGFBP-5 may play a role in the pathogenesis of atherosclerosis, which is a process of inflammatory tissue remodeling within the matrix of the arterial wall that is the top cause of cardiovascular disease and aging-related mortality in humans (136). A cross-sectional case-control study found a positive association between circulating IGFBP-5 levels and coronary heart disease (137).…”
Section: Igfbp-5 In Pathology and Disease Statesmentioning
confidence: 99%
“…The role of IGFBP-5 in both atherosclerosis and fibrosis may be linked to the induction of cellular senescence (145,151). Aged artery walls are more susceptible to atherosclerosis and hypertension which may be related to accumulation of senescent cells and the resultant compositional changes in the subendothelial matrix (136). The accumulation of senescent cells in the arteries of children with the premature aging disease Hutchinson-Gilford Progeria seems to be the cause of their severe accelerated atherosclerosis and premature death from resulting stroke or heart attack before age 20 (152,153).…”
Section: Igfbp-5 In Pathology and Disease Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the use of different endpoints across studies, combined with the lack of a necropsy report, can render an aging study incomplete ( Santulli et al., 2015 , Treuting et al., 2016 ). Similarly, the use of different paradigms of chronic stress render inter-study consistency even more difficult to achieve ( Allard and Duan, 2011 ). These are some of the critical challenges for the field in the near future; hopefully, more multi-centric collaborative research efforts may allow for the overcome of such critical obstacles.…”
Section: The Effect Of Age In the Stress Responsementioning
confidence: 99%
“…36 During aging, the increase in the cortisol/DHEAS ratio refers significantly to an increase in the neurotoxicity and probably contributes to the occurrence of age-related neurodegenerative illnesses. 37,38 Thus, higher secretions of DHEA/DHEAS considered of great importance in improving health outcomes, [39][40][41][42] including psychological status, and reduced risk of death from cardiovascular disease. [39][40][41][42] Similarly, corticosterone (CORT) levels were generally raised following stressful events and impairs in cognition/memory and stress coping which in turn lead to a reduction in the structural and functional plasticity of the brain.…”
Section: Introductionmentioning
confidence: 99%